Formulation and Evaluation of Metoprolol Succinate Orodispersible Tablets Using Directly Compressible Coprocessed Excipient of Moringa Gum - Subhranshu, Panda (Asian Journal of Pharmaceutics (AJP), 2020)
Aims: The aim of the present research work is to develop fast-dissolving tablets of metoprolol succinate applying novel directly compressible coprocessed excipient which improves the functionality and masking the undesirable properties of the drug without any chemical modification. Subjects and Methods: For the development of coprocess excipient, synthetic superdisintegrants such as crospovidone, sodium starch glycolate (SSG), and croscarmellose sodium were processed with natural disintegrants Moringa gum in varying ratios 1:1–1:4. Results: Coprocessed excipient prepared from polymers ratio of 1:1 and 1:2 have shown good physicochemical properties and pre-compression parameters such as angle of repose, bulk density, true density, and compressibility index. The post-compression parameters have shown acceptable and within the pharmacopeial limit. In vitro drug release for all the formulations F1–F12 was found in between 95% and 97% and was satisfactory. The optimized batch F2 formulated with 4% Moringa gum and 2% SSG, the drug release was found to be 97% within 2 min. Developed optimized formulations were kept for stability study for 1 month as per the ICH guidelines and found to be stable. Conclusions: The study indicates that the use of coprocessed excipient has an added advantage over individual polymers and can be used in orodispersible tablet formulations irrespective of drug type.